Multiplatform ecosystems of professional learning: The case of the #CharlasEducativas - Jeffrey P. Carpenter; Ingrid Mosquera-Gende; Paula Marcelo-Martínez (Journal of New Approaches in Educational Research)
Abstract Self-directed educator professional learning is commonplace, and such activities increasingly span multiple digital spaces and formats, and blur boundaries between online and offline. In this exploratory research, we analyze the case of the #CharlasEducativas, a dynamic professional learning ecosystem that began in 2020 and is based in Spain. We describe the platforms, modalities, and activities that comprised the #CharlasEducativas from 2020–2023, and how these different elements combine to create a multiplatform learning ecosystem. Relying upon multiple data sources, we also analyze the topics and content associated with various components of this unique ecosystem, and share participant perceptions of the #CharlasEducativas. Although the ecosystem was first developed relying mostly on YouTube and X/Twitter, the #CharlasEducativas have evolved over time to include additional platforms, and even in-person events, with different spaces functioning in overlapping and distinct ways. These spaces have been employed in synchronous and asynchronous ways, using text, images, voice, and visuals to discuss and share information on a wide array of education topics. Many participants reported perceiving the #CharlasEducativas as a space of learning and community building, and credited this learning and community with sparking reflection upon and changes in their own teaching practices. We discuss how the #CharlasEducativas reflect opportunities and challenges of contemporary educator professional learning in the context of ubiquitous social media platforms. Finally, we define implications for research and practice, highlighting the need to advance understanding of educators’ multiplatform professional learning activities.